A model of mudflow propagation downstream from the Grohovo landslide near the city of Rijeka (Croatia) - E. Žic; Ž. Arbanas; N. Bićanić; N. Ožanić (Natural Hazards and Earth System Sciences, 2015)
Mudflows regularly generate significant human and property losses. Analyzing mudflows is important to assess the risks and to delimit vulnerable areas where mitigation measures are required. The smoothed-particle hydrodynamics (SPH) model adopted here considers, in two phases, a granular skeleton with voids filled with either water or mud. The SPH depth-integrated numerical model (Pastor et al., 2009a) used for the present simulations is a 2-D model capable of predicting the runout distance, flow velocity, deposition pattern and the final volume of mudflows. It is based on mathematical and rheological models. In this study, the main characteristics of mudflow processes that have emerged in the past (1908) in the area downstream of the Grohovo landslide are examined, and the more relevant parameters and attributes describing the mudflow are presented. Principal equations that form the basis of the SPH depth-integrated model are reviewed and applied to analyze the Grohovo landslide and the propagation of the mudflow wave downstream of the landslide. Based on the SPH method, the runout distance, quantities of the deposited materials and the velocity of mudflow progression which occurred in the past at the observed area are analyzed and qualitatively compared to the recorded consequences of the actual event. Within the SPH simulation, the Newtonian rheological model in the turbulent flow regime and the Bingham rheological model were adopted and a comparison was made of the application of the Egashira and Hungr erosion law.